’Laban, Laban’: An Essay on Cooking with Yoghurt - Hourani, Afnan (Petits Propos Culinaires, 2024)
I was born in Baghdad of a Persian father and a half-Turkish mother. My mother’s other half was from Aleppo and later I married a Lebanese. This mixture enabled me to live in and travel to yoghurt eating countries most of my life and has therefore enabled me to collect traditional yoghurt recipes. The collection has now grown to the point of constituting a book, which I hope will find a publisher. In the course of my research I asked friends, relatives and their cooks for recipes and this led to many discussions about yoghurt and its different uses in Turkey, Iran and the Eastern Arab world. It is not common in North Africa, to my chagrin as I spent ten years of my life in Tunisia. I learned that the same traditional method of making yoghurt is used all over and that it is an essential part of the culture. So much so that the early Lebanese emigrants dipped bits of cloth in yoghurt and dried them in the open air. The bits of cloth were taken to their new homes in America, Brazil, Australia or wherever, and reconstituted into yoghurt to be used as starters.